2006
DOI: 10.1016/j.jtcvs.2005.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Homing of intravenously infused embryonic stem cell-derived cells to injured hearts after myocardial infarction

Abstract: Our data demonstrate that intravenously infused embryonic stem cell-derived cells homed to the infarcted heart, improved cardiac function, and enhanced regional blood flow at 6 weeks after myocardial infarction. The in vitro migration assay suggested that such a homing mechanism could be associated with locally released cytokines, such as tumor necrosis factor alpha, that are upregulated in the setting of acute myocardial infarction and heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Beeres et al [58] showed 6% improvement in ejection fraction after 6 months of treatment, while in a study by Briguori et al [59] there was no difference in ejection fraction after 1-year follow-up. Recently, noncontrolled pilot studies showed comparable results with 4-6% augmentation of ejection fraction at 3 months [41] or 1 year [42], respectively.…”
Section: Clinical Trials In Chronic Left Ventricular Systolic Dysfuncmentioning
confidence: 90%
See 1 more Smart Citation
“…Beeres et al [58] showed 6% improvement in ejection fraction after 6 months of treatment, while in a study by Briguori et al [59] there was no difference in ejection fraction after 1-year follow-up. Recently, noncontrolled pilot studies showed comparable results with 4-6% augmentation of ejection fraction at 3 months [41] or 1 year [42], respectively.…”
Section: Clinical Trials In Chronic Left Ventricular Systolic Dysfuncmentioning
confidence: 90%
“…ESCs have been studied extensively in animals. Murine and sheep models of myocardial infarction have been studied, transplanting ESCs, and in short-term follow-up demonstrating improved ejection fraction and vascularity [41,42]. Problems with ESCs, apart from the ethical concerns, include tumorigenicity, difficulty in purification, and host immune response [9].…”
Section: Pathophysiology and Preclinical Researchmentioning
confidence: 99%
“…This possibility received experimental support when ESC-derived cardiomyocytes injected into the tail vein had been shown to translocate to ischemic areas of the heart [70]. Furthermore, an in vitro study observed enhanced ESC-derived cardiomyocytes migration toward cells that over-express TNF (tumor necrosis factor), a cytokine likely to be present at the site of injury [70].…”
Section: Embryonic Stem Cells (Esc)mentioning
confidence: 99%
“…Stringent requirements for purity are particularly demanded for in vivo transplantation studies, where even a low percentage of contaminating MEFs in a large (millions) batch preparation can translate into a substantial number. This is problematic for the intravascular delivery of ES cells, which is an active front of research in tissue repair and regeneration [14,15]. Because the diameter of MEFs is greater than that of a typical capillary, they have a high likelihood of causing embolism in the capillary bed.…”
Section: Introductionmentioning
confidence: 99%